1976
DOI: 10.1073/pnas.73.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Totipotency and normal differentiation of single teratocarcinoma cells cloned by injection into blastocysts.

Abstract: A definitive test for developmental totipotency of mouse malignant teratocarcinoma cells was conducted by cloning singly injected cells in genetically marked blastocysts. Totipotency was conclusively shown in an adult mosaic female whose tumor-strain cells had made substantial contributions to all of the wide range of its somatic tissues analyzed; the clonally propagated cell lineage had therefore differentiated in numerous normal directions. The test cells were from "cores" of embryoid bodies of a euploid, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
169
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(177 citation statements)
references
References 18 publications
3
169
0
1
Order By: Relevance
“…Whereas normal stroma can postpone or prevent tumorigenesis, abnormal stromal components can promote tumor development. 28 It has been demonstrated for example, that PAR1 (as also PAR2) is expressed in the stromal microenvironment of malignant tumors whereas it is absent in both benign tumors and normal epithelium. 29 Reactive stromal myofibroblasts, local mast cells, macrophages, endothelium and vascular smooth muscle cells of the tumor microenvironment express PAR1 and likely to express FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas normal stroma can postpone or prevent tumorigenesis, abnormal stromal components can promote tumor development. 28 It has been demonstrated for example, that PAR1 (as also PAR2) is expressed in the stromal microenvironment of malignant tumors whereas it is absent in both benign tumors and normal epithelium. 29 Reactive stromal myofibroblasts, local mast cells, macrophages, endothelium and vascular smooth muscle cells of the tumor microenvironment express PAR1 and likely to express FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Even teratocarcinoma cells were found to contribute to the formation of some normal tissues when injected into blastocysts. 20 Another aspect to note in the formation of tissues from progenitor/stem cells in vivo is that adult organs are often self-sufficient, ie, they can compensate cell loss without any supply of cells from other organs. Thus, significant repopulation of exogenous hepatocyte progenitor cells in the liver was observed only when the liver was severely damaged.…”
Section: Discussionmentioning
confidence: 99%
“…By injecting embryonic carcinoma (EC) cells derived from the central portions of mouse embryoid bodies into blastocysts, Mintz and colleagues demonstrated that EC cells can contribute to the development of most of the tissues and cell lineages in the newly formed mosaics [2], [3]. These observations led them to conclude that these EC cells remain multipotent, despite being passaged in vivo as an ascites tumor for 8 years [2], [3]. Culture conditions were subsequently established that allowed the isolation of pluripotent embryonic stem (ES) cells from mouse embryos [4].…”
Section: Introductionmentioning
confidence: 99%